Novel dnaG mutation in a dnaP mutant of Escherichia coli. - Murakami, Y (1985)
Reexamination of the dnaP18 mutant strain of Escherichia coli revealed that the mutation responsible for the arrest of DNA replication and cell growth at high temperatures resides in the dnaG gene rather than in the dnaP locus as previously thought; this mutation has been designated dnaG2903.